1988
DOI: 10.1111/j.1467-8624.1988.tb03218.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing in Seven-Month-Old Infants as a Function of Risk Status

Abstract: 7-month-old full-terms and high-risk preterms (less than 1,500 grams at birth) were compared on problems of visual recognition memory and tactual-to-visual cross-modal transfer. On the visual problems, preterm infants showed significantly less differential attentiveness to novelty than full-terms. They also required longer exposure times during visual familiarization, primarily because of longer pauses between fixations. Preterms and full-terms exhibited different patterns of looking, as indicated by the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
77
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 25 publications
16
77
4
Order By: Relevance
“…Effect sizes in the studies which found significant differences between preterms and terms were predominantly medium. In Rose et al (1988), when tested with naturalistic faces and geometric 3D forms, no difference was found between 7-month-old preterms with RDS and 7-month-old terms. With abstract patterns, however, a significant difference between groups, with an effect size of d = 0.49 ( p = .01), emerged.…”
Section: Visual Habituation and Dishabituation In Preterm Versus Tmentioning
confidence: 80%
See 2 more Smart Citations
“…Effect sizes in the studies which found significant differences between preterms and terms were predominantly medium. In Rose et al (1988), when tested with naturalistic faces and geometric 3D forms, no difference was found between 7-month-old preterms with RDS and 7-month-old terms. With abstract patterns, however, a significant difference between groups, with an effect size of d = 0.49 ( p = .01), emerged.…”
Section: Visual Habituation and Dishabituation In Preterm Versus Tmentioning
confidence: 80%
“…Risk factors are listed in Table 4. They include IVH, RDS (e.g., Landry, Leslie, Fletcher, & Francis, 1985; Rose, Feldman, McCarton, & Wolfson, 1988), hyaline membrane disease (Cohen, 1981), and cardiac anomalies (Millar, Weir, & Supramian, 1991). In two studies, the nature of additional risk factors was not specified (Caron & Caron, 1981; Holmes, Reich, & Gyurke, 1989), making it difficult to draw firm conclusions about the samples.…”
Section: Visual Habituation and Dishabituation In Preterm Versus Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a robust response to visual novelty in these groups raised provocative questions about the meaning of early perceptual-cognitive changes and their possible relationship with long-term intelligence and academic success (Rose et al , 1988). While it is difficult to predict the meaning of early differences in selective visual attention, infant novelty preference scores are related to later performance on standardized tests of intelligence, (Fagan et al , 1986, Thompson et al , 1991, Fagan et al , 2007, Rose et al , 1988, Rose, et al , 2005). In addition, better infant visual recognition memory scores have been associated with enhanced comprehension and gestural communication in toddlers (Heimann et al , 2006) and improved expressive and receptive language skills during preschool and beyond (Fagan and McGrath, 1981, Rose et al , 1991, Thompson et al , 1991).…”
Section: Perinatal Risk and Effects On Visual Recognition Memorymentioning
confidence: 99%
“…Since that time, longitudinal studies of infants born prematurely with age-matched, full-term controls have demonstrated a greater incidence of behavioral, cognitive, and learning problems in infants born prematurely that persist into childhood (e.g., Anderson, Doyle, & Victorian Infant Collaborative Study Group, 2003; Grunau, Whitfield, & Davis, 2002; Pharoah, Stevenson, & West, 2003; Rose & Feldman, 1996; Taylor, Klein, Minich, & Hack, 2000) and late adolescence (e.g., Grunau, Whitfield, & Fay, 2004; Hack et al, 2002; Saigal, Hoult, Streiner, Stoskopf, & Rosenbaum, 2000). Specifically, preterm infants are slower in the processing of novel (e.g., Gardner & Karmel, 1983; Landry, Leslie, Fletcher, & Francis, 1985; Millar & Weir, 1995; Rose, Feldman, Jankowski, & Caro, 2002; Rose, Feldman, McCarten, &Wolfson, 1988) and contingent stimulation (e.g., Gekoski, Fagen, & Pearlman, 1984; Millar, Weir, & Supramaniam, 1992; Ramey, Heiger, & Klisz, 1972), which may be due, in part, to differences in brain function (e.g., Herbert, Eckerman, Goldstein, & Stanton, 2004) or difficulties in arousal regulation (e.g., Mayes, 2000; Millar & Weir, 2007). …”
mentioning
confidence: 99%